Color Inspection Label Checking System for Aimar Printer Model at PT. Indonesia Epson Industry (IEI) - Mardiani, Eri; Akbar Ramadhan, Ferdan (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Consumer purchases are influenced by four main psychological factors including motivation, perception, learning, and beliefs and attitudes. The desire or motivation of consumers to make purchases according to certain needs and times. So that the perception of a motivated consumer will be ready to act to make a purchase, and usually consumers will be motivated based on the influence of perception on a particular situation. Here the company wants to increase consumer or buyer satisfaction and the label is a part of the product in the form of a description of both pictures and words which functions as a source of product and seller information. Labels generally contain information in the form of product names or brands, raw materials, composition additives, nutritional information, expiration dates, product contents, and legality information. performance achievement of company targets. This study aims to help understand quality control issues for the assembly process, especially printers for types of defects at the printing stage. As well as providing references for people who need quality labels and Color Inspection Label Checking Systems and as additional input for quality reporting performance analysis for companies